Plan estratégico para el desarrollo institucional de la unidad educativa Zapotal, cantón Ventanas, periodo 2015-2019 - García Aristega, Denisse Yanela (2016)
This research has been prepared in Zapotal Education Unit in order to improve the institutional development through the development and implementation of a strategic plan for the period 2015-2019 to be held the same based on the particular issue both internally and externally in the institution. It is intended to continue on the path of promoting educational excellence and institutional development as it is very important that every institution has a strategic plan to establish new lines of action that contribute to continuous improvement, allowing regulating and measuring activities They develop within it in order to achieve objectives. In carrying out the strategic plan was discussed in an orderly and coherent functions, goals, objectives, strategies, policies, conditions and rules in time and space, as well as the instruments, mechanisms and actions to reach the desired end. Then this study will aim to demonstrate through internal and external analysis, where it is currently located, visualize where you want to go and trace the path that leads from one side to another. Based on the interview with the Director of the Education Unit Zapotal Atty. Carlos Cesar Villalba, we determined that there is a good relationship and work environment between both administrative staff and teaching them to join forces to achieve the objectives set educational quality, while one of the weaknesses that we noted is the lack of commitment Parents of the institution which causes a lack of communication between teachers, students and that as parents should be aware of the problems that arise within the educational institution where drugs, alcohol and other aspects damage the appropriate training of students. If you want to achieve educational quality they must all be committed to counteract these damaging factors for the student society. It is now clear that the Education Unit "Zapotal" lacks a strategic plan defined for this reason the need to carry out the preparation, which can be set improvement alternatives for the benefit of the institution.